2016
DOI: 10.5152/npa.2016.14862
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cognitive Parameters between Bilateral and Unilateral Hippocampal Sclerosis

Abstract: Our study revealed that bilateral involvement of the hippocampi was correlated with a poor cognitive performance. Retrieval failure, rather than a total recall problem, in the memory of the patients resembles a more diffuse involvement not only limited to limbic structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In our study that compared cognitive findings in patients having bilateral HS with those having unilateral HS, we found a significant difference in terms of verbal memory involvement among the patients. Besides, we showed that there is no difference in terms of visual memory decline (5). We also determined that mental retardation was frequent in patients with voltage-gated potassium channel antibodies in our large HS cohort screened for various neuronal autoantibodies.…”
mentioning
confidence: 71%
“…In our study that compared cognitive findings in patients having bilateral HS with those having unilateral HS, we found a significant difference in terms of verbal memory involvement among the patients. Besides, we showed that there is no difference in terms of visual memory decline (5). We also determined that mental retardation was frequent in patients with voltage-gated potassium channel antibodies in our large HS cohort screened for various neuronal autoantibodies.…”
mentioning
confidence: 71%
“…Details of neuropsychological results are published elsewhere. 19 Drug resistance was defined according to the criteria published by Kwan et al 20 For all operated patients, postoperative follow-up duration and duration of seizure freedom were investigated if present. The prognosis of the patients was classified according to the Engel classification.…”
Section: Clinical Data Collectionmentioning
confidence: 99%